Hubungan Antara Secure Attachment dan Kemandirian dengan Motivasi Berprestasi pada Remaja - Sri Rahmadani; Nefi Darmayanti; Irna Minauli (Universitas Medan Area, 2020)
The purpose this study was to determine the relationship between secure attachment with achievement motivation, the relationship between autonomy with achievement motivation, and the relationship between secure attachment and autonomy with achievement motivation in adolescents students. The population of this research was students of class X, XI and XII Madrasah Aliyah Negeri (MAN) Tebing Tinggi. The sample was 103 students were take by stratified random sampling technique. This study used secure attachment scale, autonomy scale, and achievement motivation scale. Double regression analysis showed FCOUNT 33, 482 with p = 0,000 (p0,005). The result indicate that there was significant correlation between secure attachment and autonomy with achievement. Patrially, there is a significant relationship secure attachment with achievement rxy = 0,365 with p 0,01 and there is a significant relationship between autonomy with achievement motivation rxy = 0,361 with p 0,01. R2 square value was 0, 527 it means that secure attachment and autonomy simultaneously contribute 52,7% toward achievement motivation.